2019
DOI: 10.1620/tjem.248.115
|View full text |Cite
|
Sign up to set email alerts
|

Worsening Health Status among Evacuees: Analysis of Medical Expenditures after the 2011 Great East Japan Earthquake and Nuclear Disaster in Fukushima

Abstract: After Fukushima disaster in 2011, the health status of the region's residents deteriorated. We analyzed the health status, care needs, and access to health services among evacuees and non-evacuees using healthcare expenditure (for self-employed and unemployed individuals aged < 75 years) and long-term care expenditure (mainly for individuals aged ≥ 65 years). Fukushima Prefecture was divided into four areas according to their evacuation status: non-EOAs (municipalities that did not include evacuation order are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Previous studies have shown that the LTC costs for residents over 65 years in the former evacuation areas in Fukushima prefecture were approximately 1.5 times higher in 2012-2014 than before the earthquake. 3,6 This was caused by a marked increase in the utilization ratio of mild-degree LTC presumably due to the loss of informal at-home care. Currently, there is not enough information on whether the loss of informal care is more prominent in the evacuee or returnee groups hence, more information on family members is needed to properly understand the health care needs of those living in former evacuation areas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the LTC costs for residents over 65 years in the former evacuation areas in Fukushima prefecture were approximately 1.5 times higher in 2012-2014 than before the earthquake. 3,6 This was caused by a marked increase in the utilization ratio of mild-degree LTC presumably due to the loss of informal at-home care. Currently, there is not enough information on whether the loss of informal care is more prominent in the evacuee or returnee groups hence, more information on family members is needed to properly understand the health care needs of those living in former evacuation areas.…”
Section: Discussionmentioning
confidence: 99%
“…Ueda et al (2019) used the data for evacuees of the nuclear power plant accident and identified that insufficient sleep and heavy drinking (≥ 4 drinks per day) were significant risk factors for the incidence of problem drinking in both men and women. Hasegawa et al (2019) revealed the increases in healthcare and long-term care expenditure, possibly because of the poor health status of the evacuees following the evacuations, reduced availability of informal care provided by family members and neighbors, and reduced patient copayments. The recovery and reconstruction are still on-going after GEJE.…”
Section: Articles Related With Geje In Tjem After 2011mentioning
confidence: 99%
“…A systematic review revealed psychological burdens such as a deterioration in mental health [21] and an increase in prevalence of post-traumatic stress disorder (PTSD) [22], as well as deterioration in health due to living in an evacuation center or a worse living environment [23], an increase in frailty risk [24], spread of pneumonia [25], and an increase in the number of people with subjective symptoms such as gastrointestinal and/or musculoskeletal symptoms [26].…”
Section: Factors Causing Increase In Long-term Care Certification Ratmentioning
confidence: 99%
“…Disaster survivors, and especially those aged 75 years or older, sustained not only direct injuries from the earthquake, but also deterioration in their living environments and psychological effects such as PTSD, as mentioned earlier. Informal care from family and others also declined [23], resulting in activity limitations. Together, these may have led to an increase in long-term care requirements for those with minor and medium need.…”
Section: Factors Causing Increase In Long-term Care Certification Ratmentioning
confidence: 99%